Civil Procedure in Syariah Subordinate Court, Kedah Darul Aman: Implementation of the Sulh Council under the Movement Control Order: (Prosiding Mal di Mahkamah Rendah Syariah: Kajian Pelaksanaan Majlis Sulh di Negeri Kedah sewaktu Perintah Kawalan Pergerakan (PKP)) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The management of civil claims in the Syariah Court usually takes a certain period of time to be resolved. As an alternative dispute resolution mechanism, Sulh is suggested for the resolution of disputes between parties. The first objective of this study is to identify the management of civil cases, especially those that go through the Sulh Council during the period of the Movement Control Order (MCO). The second objective is to analyze the mechanism of success at the Sulh Council during the implementation of MCO in the Syariah Subordinate Court of Kedah Darul Aman. The methodologies used in this legal study are interview as well as content analysis collected through enactments, rules and library research. The findings of the study showed that the process of the Sulh Council, which saves time and costs compared to trials in open court, are among the factors of successful settlement agreements recorded. The findings also revealed that some of the parties who were affected by the implementation of MCO agreed that Sulh Council is an effective mechanism to resolve disputes by mutual agreement according to the needs and interests of both parties. Meanwhile, in managing online cases, the current maximum use of online technology should be expanded so that justice can be maintained in cases that go through Sulh Council or otherwise as an alternative to physical presence in Syariah Court.Keywords: Civil Procedure, Sulh Council, Syariah Subordinate Court, Movement Control Order, Kedah Darul Aman